Estudio de las necesidades metrológicas del sector productivo en la región del nororiente colombiano (2006)
For the north-east part of Colombia, it is of vital importance, to have an indicator of the form of production, commerce, academe and research, wich make their measurements, with the purpose of formulating strategies and policies that will allow the productive sector to optimize their functions, to know their strengths and weaknesses with respect to the calibrate instruments and to implement projects necessary to develop the suitable processes introduced the Metrology. Based on the investigation by interviews, this article presents an analysis of the actual state of the productive sector of the north-east part of Colombia, with respect to the handling and interpretation of concepts associated with the Metrology like quality, measurements, quality control, calibration, accreditation of laboratories, traceability,  certification, etc.